2018
DOI: 10.1137/18m1166833
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Reconstruction Artifacts from Arbitrary Incomplete X-ray CT Data

Abstract: This article provides a mathematical analysis of singular (nonsmooth) artifacts added to reconstructions by filtered backprojection (FBP) type algorithms for X-ray CT with arbitrary incomplete data. We prove that these singular artifacts arise from points at the boundary of the data set. Our results show that, depending on the geometry of this boundary, two types of artifacts can arise: object-dependent and object-independent artifacts. Object-dependent artifacts are generated by singularities of the object be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 55 publications
7
62
0
Order By: Relevance
“…Test 2. In this case, we set Ω = (−1, 1) × (3,5). The distance between the source line Γ d and the domain Ω is 3, which is three times larger than the distance in test 1.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Test 2. In this case, we set Ω = (−1, 1) × (3,5). The distance between the source line Γ d and the domain Ω is 3, which is three times larger than the distance in test 1.…”
Section: 3mentioning
confidence: 99%
“…The missing data leads to the instability of the reconstruction. We cite some important papers [1,5,13,30,31] and references therein that characterize and (or) introduce the strategies to reduce the resulting artifacts, which appear in the reconstructed image. To treat the case of incompleteness, one might non-rigorously fill the missing data by the number 0, see figures 2-4 in [5].…”
Section: Introductionmentioning
confidence: 99%
“…We hope that our framework for limited angle CT will spark further interest in applying similar ideas to other inverse problems. We anticipate that this might be particularly fruitful for problems, where larger amounts of data are not acquired in the measurements, as it is for instance the case in region of interest and exterior tomography [6]. Furthermore, we have observed that we could improve the learning phase by optimizing over a more sophisticated loss function defined over the image domain or by adding additional regularizers.…”
Section: Resultsmentioning
confidence: 99%
“…This is for example the basis of geometrical tomography [12] where the singularities of an attenuation are reconstructed from the singularities of its Radon transform. Furthermore this provides a framework for the description of artifacts that arise from limited data in transmission tomography [3,5].…”
Section: Tomographymentioning
confidence: 99%